2019
DOI: 10.12927/hcpol.2019.25982
|View full text |Cite
|
Sign up to set email alerts
|

The Career Outcomes of Health Services and Policy Research Doctoral Graduates

Abstract: Objective: To examine the career outcomes of 20 years of PhD graduates from Canadian health services and policy research (HSPR) doctoral training programs. Methods: The deans of the doctoral training programs were invited to participate in this national cohort study. A standardized career-tracking template was developed. Internet searches of publicly accessible sources were used to track graduates' employment. Descriptive analyses summarized PhD program characteristics and current employment. Results: Of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 19 publications
0
13
0
1
Order By: Relevance
“…An enriched core competency framework for health services and policy research (HSPR) doctoral and post-doctoral training was introduced in Canada in 2016 (Bornstein et al 2018;CHSPRA TMWG 2015). Its goal was to align the competencies emphasized in doctoral curriculum with the skills needed to maximize the impact of health services and policy research (HSPR) graduates in the diverse range of employment sectors and roles they are entering based on employment trends (see McMahon et al 2019b) and emerging career opportunities, such as embedded scientist roles within organizations seeking to be learning health systems (Reid 2016). The enriched core competency framework maintains emphasis on rigorous scholarly training and research and analytic skills but also introduces a core suite of professional skills that are demanded in the non-academic labour market and necessary to effect change and make an impact in applied health system settings ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…An enriched core competency framework for health services and policy research (HSPR) doctoral and post-doctoral training was introduced in Canada in 2016 (Bornstein et al 2018;CHSPRA TMWG 2015). Its goal was to align the competencies emphasized in doctoral curriculum with the skills needed to maximize the impact of health services and policy research (HSPR) graduates in the diverse range of employment sectors and roles they are entering based on employment trends (see McMahon et al 2019b) and emerging career opportunities, such as embedded scientist roles within organizations seeking to be learning health systems (Reid 2016). The enriched core competency framework maintains emphasis on rigorous scholarly training and research and analytic skills but also introduces a core suite of professional skills that are demanded in the non-academic labour market and necessary to effect change and make an impact in applied health system settings ( Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The Health System Impact (HSI) Fellowship program was designed in 2016 to fill a gap in Canada' s HSPR doctoral and post-doctoral training programs. The Training Modernization Working Group (TMWG) of the Canadian Health Services and Policy Research Alliance (CHSPRA) found that although a very high proportion of Canada' s HSPR PhD graduates enter careers in research and administrative jobs in health system organizations rather than in professorial positions in university departments (see McMahon et al [2019b] in this issue), universities are continuing to train them in traditional ways, with a focus on academically relevant skills and university careers. Accordingly, through consultations with the TMWG and key stakeholders across the country, CIHR-IHSPR designed a new, competitive national program of embedded fellowships that prepares PhD trainees and post-doctoral fellows for careers and impact in a diverse array of health system settings.…”
Section: Core Objectivesmentioning
confidence: 99%
“…The HSI Fellowship program has five distinctive features: (1) It involves a modernized, pan-Canadian curriculum focused on a set of enriched core competencies (e.g., leadership, change management) designed to prepare fellows for success in careers outside the university (see Bornstein et al [2018] and McMahon et al [2019b] in this issue), and they include a dedicated professional development allowance to support fellows' pursuit of these core competencies; (2) It includes substantial experiential learning placements that embed fellows in a "host partner organization" that also provides co-funding for a program of work designed to address a high-priority challenge (an "impact goal") identified by the organization; (3) It involves co-supervision and mentorship by a health system leader and an academic leader; (4) It permits fellows to protect up to 30% of their time for academic research within the university in order to stay at the forefront of their field and bring the latest academic developments to bear on "real-world" challenges; and (5) It brings all the funded fellows, and their health system and academic mentors, together in a national cohort whose annual in-person meeting and quarterly webinar sessions contribute to training, peer-to-peer collaborations and cross-cohort learning. These innovative features come together in a two-year fellowship for post-doctoral fellows and a one-year fellowship for doctoral trainees that are jointly funded by federal and provincial funders and by the host partner organizations.…”
Section: Innovative Featuresmentioning
confidence: 99%
“…Therefore, PHC researchers need to have a complex and comprehensive set of skills for engaging effectively in high impact research. These individuals need to be able to span the boundaries of the academic world and those of the broader health care system, and be prepared to work in interdisciplinary teams in non-academic settings [ 21 23 ]. Despite this, training of PHC researchers still occurs in the silos of their own discipline, with few opportunities for individuals from different PHC disciplines to come together.…”
Section: Introductionmentioning
confidence: 99%